UNDERSTANDING ELECTRONIC LETTER WRITING FOR VOCATIONAL SCHOOL STUDENTS: MATERIAL AND PRACTICE - Perdani, Yella Dezas; Indrawati, Desi; Sofiani, Nana; Istanti, Wati (SEEIJ (Social Economics and Ecology International Journal), 2025)
Vocational school students are intended to be informed and instructed on the art of composing business emails through this community service activity. It employed service learning (SL), an approach that combined academic instruction with community service. The service learning was conducted at one vocational school in Bandung City, West Java. There were twenty-two students who participated in this service learning. Besides, the learning service was two hours long. Moreover, the research used qualitative design to describe the students’ effectiveness of the service learning in improving the students’ email writing ability. Observation was used as a data collection technique. The findings implied that the students showed significant engagement from the beginning of service learning. Besides, they also got involved in a group discussion after the practical practices. Other findings indicated that the students gave positive feedback in which the interactive and participatory format of service learning enhanced their engagement and motivation. Finally, the traning, material and practices gave beneficial experience for students in comprehending business email protocols, equipping them for the professional environment post-graduation.